PENGEMBANGAN CIVIC DISPOSITION DALAM MENGATASI MASALAH BELAJAR SISWA DI SMP NEGERI 7 AMBON - Damayana, Nessa Nur Aulia; Sialana, Fatimah; Patmawati, Susi Anita (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Education plays a crucial role in shaping a generation that is both qualified and has strong character, which in turn supports the progress of a nation. Amid the waves of 21st-century globalization, Indonesia faces various social, cultural, and moral challenges, including an increase in social problems among students, such as fights, bullying, cheating, and other violations of school rules. The instilling of national character values and civic disposition in schools has become vital in addressing these issues. Civic Education (PKn) is expected to shape students' character to become intelligent, skilled, and responsible citizens. This study aims to examine the role of civic disposition in addressing social problems at SMP Negeri 7 Ambon, focusing on the development of better student character and behavior. Through a qualitative approach, the research reveals that the consistent application of civic disposition can reduce deviant behavior at school and foster more responsible citizens. The benefits of this research are expected to serve as a reference in the development of student character, particularly in addressing social challenges within the school environment. Practically, this study can help teachers design effective teaching strategies to develop civic disposition and tackle social problems in schools.